2011
DOI: 10.1172/jci57873
|View full text |Cite
|
Sign up to set email alerts
|

Circulating glucose levels modulate neural control of desire for high-calorie foods in humans

Abstract: Obesity is a worldwide epidemic resulting in part from the ubiquity of high-calorie foods and food images. Whether obese and nonobese individuals regulate their desire to consume high-calorie foods differently is not clear. We set out to investigate the hypothesis that circulating levels of glucose, the primary fuel source for the brain, influence brain regions that regulate the motivation to consume high-calorie foods. Using functional MRI (fMRI) combined with a stepped hyperinsulinemic euglycemic-hypoglycemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
163
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 179 publications
(174 citation statements)
references
References 43 publications
8
163
3
Order By: Relevance
“…These lower glucose levels with liraglutide are, however, unlikely to explain our results, as lower circulating levels of glucose are associated with increased activation in insula and putamen during the viewing of food pictures (38). Despite the slightly lower glucose levels with liraglutide treatment in the current study, we observed a decreased CNS activation in insula and putamen.…”
Section: Discussioncontrasting
confidence: 83%
“…These lower glucose levels with liraglutide are, however, unlikely to explain our results, as lower circulating levels of glucose are associated with increased activation in insula and putamen during the viewing of food pictures (38). Despite the slightly lower glucose levels with liraglutide treatment in the current study, we observed a decreased CNS activation in insula and putamen.…”
Section: Discussioncontrasting
confidence: 83%
“…The caudate has direct physical and functional connections with executive control regions in the frontal cortex including the medial, ventral, and dorsolateral PFC (22,23). Among HC individuals, mild hypoglycemia was sufficient to elicit changes in the caudate, cortical regions such as the vmPFC and vlPFC, and the insula, which is consistent with previous studies that have shown that the caudate, PFC, and insula are responsive to changes in circulating glucose levels (5,12,24,25). In contrast, T1DM-Aware individuals had altered patterns of cortico-striatal activity with no significant changes in the caudate or insula during hypoglycemia.…”
Section: Neural Responses To Mild Hypoglycemiasupporting
confidence: 89%
“…We have previously reported using the glucose clamp technique together with functional magnetic resonance (fMRI) imaging, visual food cues, and behavioral measures that brain regions involved in stimulating motivation to eat are exquisitely sensitive to small reductions in glucose. In healthy humans, mild reductions in plasma glucose (~68 mg/dl) that were not sufficient to increase counterregulatory hormones were sufficient to activate hypothalamic blood flow (4) as well as modulate brain motivation/reward and executive control responses to food cues, which in turn resulted in a greater craving for high-calorie foods (5).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of factors in the development and maintenance of obesity are currently discussed, including psychological (e.g., Weygandt et al, 2012;Rothemund et al, 2007;Torres et al, 2007;Ng & Jeffrey, 2003;Rodin et al, 1989), behavioural (e.g., Hays et al, 2008;Bellisle et al, 2004), genetic (e.g., Dina et al, 2007;Frayling et al, 2007), and endocrinological (e.g., Page et al, 2011;Ahima, 2008;Rosenbaum et al, 2008;Farooqi et al, 2007;Klok et al, 2007). Within the latter framework, also (insufficient) cerebral insulin suppression during stressful events is discussed, a topic especially referred to in the literature on the 'selfish-brain theory' (c.f.…”
Section: Introductionmentioning
confidence: 99%